Models of dual vocational education: sources of mutual inspiration - Grollmann, Philipp [Verfasser] (My University, 2017)
"In this article Dr Philipp Grollmann, Deputy Head of the Internationalisation / Monitoring of VET Systems at the BIBB, provides an interesting account on the models of the dual system by telling us how they evolve constantly and how they can be applied in other economies." (Excerpt; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; Berufsbildungssystem; Internationaler Vergleich; Bundesrepublik Deutschland; Indien